PENGARUH WORKING FROM HOME DAN TRANSFORMATIONAL LEADERSHIP TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Kantor FinanceGov) - Saroni, Imam; Satrya, Aryana; Listyarini, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The demands of Bureaucratic Reform and the ministry of finance faced the challenges of the COVID-19 Pandemic "accelerate" the implementation of New Thinking of Working in all its organizational units including FinanceGov within the Regional Office of the Ministry Finance of East Java Province in order to improve employee performance, especially during the pandemic. The results of previous studies Most Implementations of Working from Home and Transformational Leadership are able to improve employee performance. In this regard, the researcher conducted research on 152 employees in the FinanceGov unit by using online surveys and direct interviews with Human Resources managers in the unit. by Job Satisfaction can improve employee performance. Furthermore, this study is quantitative using data processing with SMARTPLS, as for the results of this study are Working from Home and Transformational Leadership affect employee performance, and job satisfaction is able to play its role as a mediating variable that strengthens the impact of Working from Home and Transforming  Leadership in  employee performance.